Reseña: Íñigo Moré, The Borders of Inequality. Where Wealth and Poverty Collide - Izquierdo Álvarez, Sara (Boletín de la Real Sociedad Geográfica; Núm. CLII (2017), 2018)
Íñigo MORÉ, The Borders of Inequality. Where Wealth and Poverty Collide, Tucson: The University of Arizona Press, 2011. 192 pp. ISBN 978-0-8165-3162-2